2017
DOI: 10.13075/ijomeh.1896.00709
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to excessive sounds and hearing status in academic classical music students

Abstract: Objectives: The aim of this study was to assess hearing of music students in relation to their exposure to excessive sounds. Material and Methods: Standard pure-tone audiometry (PTA) was performed in 168 music students, aged 22.5±2.5 years. The control group included 67 subjects, non-music students and non-musicians, aged 22.8±3.3 years. Data on the study subjects' musical experience, instruments in use, time of weekly practice and additional risk factors for noise-induced hearing loss (NIHL) were identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
9
0
4
Order By: Relevance
“…Even if loud classical music poses a lower risk of NIHL than a similar dose of heavy metal music or industrial noise, the negative result of Karlsson et al [123] has been overturned by many subsequent studies [118,120,[127][128][129][130][131][132][133][134][135][136][137][138][139][140]. For example, Royster et al [118] found that Chicago Symphony Orchestra musicians were exposed at just above the NIOSH REL during their 15 h of weekly rehearsals and performances (not counting solitary practice).…”
Section: Live Music Performances and Rehearsalsmentioning
confidence: 99%
“…Even if loud classical music poses a lower risk of NIHL than a similar dose of heavy metal music or industrial noise, the negative result of Karlsson et al [123] has been overturned by many subsequent studies [118,120,[127][128][129][130][131][132][133][134][135][136][137][138][139][140]. For example, Royster et al [118] found that Chicago Symphony Orchestra musicians were exposed at just above the NIOSH REL during their 15 h of weekly rehearsals and performances (not counting solitary practice).…”
Section: Live Music Performances and Rehearsalsmentioning
confidence: 99%
“…Niewiele jest także doniesień przedstawiających ewentualne różnice między studentami a profesjonalnymi muzykami dotyczące rozpowszechnienia poszczegól-nych rodzajów dolegliwości [20,21]. Ustalenie, jakie problemy zdrowotne pojawiają się jeszcze przed rozpoczęciem kariery zawodowej, pozwoliłoby na określe-nie potrzeb w zakresie profilaktyki mogącej uchronić przyszłych muzyków-pracowników przed dolegliwościa-mi czasowo lub trwale ograniczającymi ich zdolność do pracy.…”
Section: Wstępunclassified
“…Studenci muzyki, podobnie jak profesjonalni muzycy, przez większą część czasu związanego z wykonywaniem swoich obowiązków są jednak narażeni na hałas, co skutkuje częstszym występowaniem u nich problemów ze słuchem w porównaniu z rówieśnikami niezwiązanymi na co dzień z wykonawstwem muzycznym [21]. Pawlaczyk-Łuszczyńska i wsp.…”
Section: Dolegliwości Słuchoweunclassified
See 1 more Smart Citation
“…Pawlaczyk-Łuszczyńska et al [ 16 ] studied a group of 168 academic orchestra students with 6.5% of percussionists ( n = 11). They gathered information about SPL during individual and group playing.…”
Section: Related Workmentioning
confidence: 99%